Variation in rheological characteristics and microcosmic composition of the sewage sludge after microwave irradiation. (1st April 2017) - Tang, Bing; Feng, Xianfeng; Huang, Shaosong; Bin, Liying; Fu, Fenglian; Yang, Kanghua
Abstract: The objective of the presented investigation was to determine the effects of microwave irradiation (MV irradiation) on the rheological characteristics of sewage sludge, and tried to explain the variation of apparent behaviors from a viewpoint of microcosmic composition. The results revealed that, from a macroscopic perspective, several rheological characteristics of sludge, including the apparent viscosity, limit viscosity and rheogram, were markedly changed by MV irradiation, and four rheological models (Power law, IPC Paste, Casson andNCA/CMA Casson ) were found to be quite suitable for describing the rheological behaviors of sewage sludge before and after MV irradiation. However, from a microscopic perspective, MV irradiation effectively disintegrated multi-pole macromolecules contained in sludge, which reliably reduced the size of sludge particles and narrowed the particle size distribution. Even though the concentration of total solids increased following MV irradiation due to the evaporation of water, the content of macromolecules such as protein and polysaccharides in the remaining solids actually decreased. The changes in water content, chemical composition and particle size of sludge lead to variations of the total solids and the absolute value of zeta potential, which may be an essential reason for changing the rheological characteristics, including yield stress, thixotropy and apparent viscosity. Graphical abstract: Highlights: Effects of microwave on the rheological characteristics of sludge were revealed. Microwave markedly changed the rheological characteristics of sludge. The microcosmic composition of sludge determined its apparent rheological behavior.